2015
DOI: 10.1007/s13277-015-3616-7
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 2A core promoter region genetic polymorphism and its impact on the risk, tumor behavior, and recurrences of sinonasal inverted papilloma (Schneiderian papilloma)

Abstract: Inverted papillomas are a unique group of locally aggressive benign epithelial neoplasms in the nasal cavity and paranasal sinuses arising from the Schneiderian mucosa. Metallothioneins are sulfhydryl-rich heavy metal-binding proteins required for metal toxicity protection and regulation of biological mechanisms including proliferation and invasion. The goal of this study was to identify three SNPs at loci −5 A/G (rs28366003) and −209 A/G (rs1610216) in the core promoter region and at locus +838 C/G (rs10636) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The association of single nucleotide polymorphisms (SNPs) at loci -5 A/G (rs28366003) and -209 A/G (rs1610216), as well as +838 C/G (rs10636) in the 3′ untranslated region of the MT2 gene were investigated in sinonasal inverted papillomas, which are locally aggressive benign epithelial neoplasms in the cavity and paranasal sinuses (Starska et al, 2015a). MT2 mRNA expression and Cd and Cu concentrations were negatively correlated with the -5 A/G SNP (Starska et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The association of single nucleotide polymorphisms (SNPs) at loci -5 A/G (rs28366003) and -209 A/G (rs1610216), as well as +838 C/G (rs10636) in the 3′ untranslated region of the MT2 gene were investigated in sinonasal inverted papillomas, which are locally aggressive benign epithelial neoplasms in the cavity and paranasal sinuses (Starska et al, 2015a). MT2 mRNA expression and Cd and Cu concentrations were negatively correlated with the -5 A/G SNP (Starska et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Starska et al [47], provides evidence for implicating MT2A polymorphisms in the development of SNIP. The findings also illustrate the key role played by the MT2A gene in inducing an aggressive Schneiderian papilloma phenotype.…”
Section: Eur Arch Otorhinolaryngolmentioning
confidence: 98%
“…The transcription of the MT gene (changes in the MT2A gene) is activated in response to a wide range of stimuli, including oxidative stress inducing agents, cytokines, hormones and various chemical agents [47]. Starska et al [47], provides evidence for implicating MT2A polymorphisms in the development of SNIP.…”
Section: Eur Arch Otorhinolaryngolmentioning
confidence: 99%
“…In recent years, ROS have generally been described as second messengers because of cellular signaling cascades and pathophysiological processes, such as proliferation, gene expression, adhesion, differentiation, senescence, apoptosis and necrosis [ 20 , 21 ], which are mediated by activated MAPKs [ 22 , 23 , 24 , 25 ]. Massive studies have revealed that oxidative stress played an important role in the pathogenesis of various diseases, such as coronary heart diseases (CHDs) [ 26 , 27 , 28 ], neurodegenerative disorders [ 29 , 30 ], cancer [ 31 , 32 , 33 ], and aging [ 34 , 35 ]. Overall, more evidences have indicated that MT2A, as a free radical scavenger, might protect cells and tissues from oxidative stress.…”
Section: Introductionmentioning
confidence: 99%